(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Bioethanol from lignocellulosic biomass is environmentally friendly and a renewable source of energy. This study used delignification as a pretreatment process to obtain the optimum conditions for reducing sugar production. The selected delignification parameters, including temperature (oc), time(hours) sodium chlorite concentration (g/dm3) and Volume of acetic acid (cm3). The Optimum conditions for delignification were: 70oc, 6 hr at -0.1 g/ dm3 sodium chlorite concentration and acid-3 cm3 of acetic. The R2 value obtained from the correlation between reducing sugar concentration and time was R2 =0.796 The maximum bioethanol concentration was at 66h and the bioethanol productivity was 0.0304 g/L/h. The result obtain pointed that, the Acanthospermum hispidum can be used for both economic and environmental footprint studies and real world application.